Public Universities' routes to excellence - New Sunday Times, Michael Sun (2007)
Universiti Putra Malysia (UPM) has organised a high-profile public lecture by 1991 Nobel Laureate professor in Chemistry, Richard Ernst, on Sciences and Our Future, at UPM, Serdang on July 20.